Answer:
The desired expression is −30+ (−70) + (−40) or −70 + (−40) + (−30)
Explanation:
Here, the given expression is −30+(−40)+(−70)
Let us assume here, X = (-30)
Y = (-40) and Z = (-70)
So, the given expressions is of the form X + Y + Z
Commutative Property states that for any number A, B and C:
A+ (B+C) = (A+B) + C
So, here ( X+Y) + Z = X+ (Y +Z)
⇒The given expression can also be written as
−30+ (−70) + (−40), or, −70 + (−40) + (−30)
Hence, the desired expression is −30+ (−70) + (−40), or, −70 + (−40) + (−30)